Complete Blood Count Reference Values of Cord Blood in Taiwan and the Influence of Gender and Delivery Route on Them - Yu-Hsun Chang; Shang-Hsien Yang; Tso-Fu Wang; Teng-Yi Lin; Kuo-Liang Yang; Shu-Huey Chen (Pediatrics and Neonatology)
Cord blood banking has become more popular in recent years. Checking cord blood complete blood count (CBC) and white blood cell (WBC) differential counts (DCs) is essential before cryopreserving the cord blood units. Therefore, establishing the normal reference values of cord blood CBC and WBC DC is important in clinical practice and research. Objectives: To obtain a large-scale population-based normal CBC and WBC DC reference values of healthy neonates’ cord blood from a public cord blood bank and to investigate the influence of the gender and delivery route. Methods: From September 2001 to November 2006, the cord blood of healthy Taiwanese neonates with gestational age 36 weeks and more were collected by Tzu Chi Cord Blood Bank with written informed consents. All cord blood samples were analyzed by Sysmex XE2100 automated hematology analyzer (Sysmex Corporation, Kobe, Japan) to obtain the CBC. The WBC DC was calculated by manual method. We used Student’s t test and Mann-Whitney U test for investigating the influences of gender and delivery route on the CBC and WBC DC reference values. The results were presented by mean±standard deviation or 2.5–97.5th percentiles. Results: In the study period, totally 5602 cord blood samples were collected eligibly for analysis. The cord blood CBC and WBC DC normal reference values were calculated. The female neonates had significantly higher mean corpuscular volume, platelet count, and WBC count, but lower red blood cell (RBC) count, hemoglobin (Hb), hematocrit, and mean corpuscular Hb concentration values (p<0.001). Newborns through vaginal delivery had significantly higher RBC count, Hb, hematocrit, platelet count, and WBC count (p<0.001). The percentages of some different types WBC were significantly influenced by gender and delivery routes. Male babies had higher lymphocyte, monocyte, eosinophil, basophil, and nucleated RBC ratios than the female neonates. Newborns through cesarean section had significantly lower neutrophil, monocyte, and nucleated RBC ratios, but higher lymphocyte and eosinophil ratios, than newborns through vaginal delivery. Conclusion: We successfully obtained the normal CBC and WBC DC reference values of the cord blood in Taiwan. Gender and delivery routes were important confounding factors that influenced the cord blood CBC and WBC DC values.